Thermosensitive intelligent control type functional master batch and preparation method thereof

By using molybdenum-tungsten doped tungsten oxide and molybdenum-doped titanium oxide materials in the functional masterbatch, combined with graphene oxide, a thermally sensitive intelligent control functional masterbatch that can regulate infrared light at different temperatures was prepared, and the current solution was solved. There is a problem of insufficient regulation of thermal insulation materials in the technology, which has achieved sensitive regulation of infrared spectroscopy and improved thermal insulation performance.

CN119264652APending Publication Date: 2025-01-07SHANGHAI HUZHENG IND CO LTD

Patent Information

Application Number
CN202411390724.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing thermal insulation masterbatch is difficult to achieve rapid and accurate regulation when the ambient temperature changes, and cannot meet the transmission or reflection needs of infrared light in different seasons, and the material is not functional and practical.

Method used

Thermal-sensitive intelligent control composite particles are made of molybdenum-doped tungsten oxide and molybdenum-doped titanium oxide materials, combined with graphene oxide, and combined with titanium-based coupling agent with plastic matrix to prepare the product to be able to be lower than the phase change temperature. When infrared transmission is transmitted, the functional masterbatch reflects infrared at higher than the phase transition temperature.

Benefits of technology

It realizes sensitive regulation of infrared spectroscopy, improves thermal insulation performance and aging resistance, and is suitable for film applications with stability and high definition in multiple fields, including automobiles, construction and agriculture.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005072342290000061
    Figure BDA0005072342290000061
Patent Text Reader

Abstract

The invention discloses a thermosensitive intelligent control type functional master batch and a preparation method thereof. The thermosensitive intelligent control type functional master batch is prepared by mixing, extruding and granulating thermosensitive intelligent control composite particles, a coupling agent and a plastic matrix, the plastic matrix accounts for 79.5-94.9 wt%, the thermosensitive intelligent control composite particles account for 5-20 wt%, and the coupling agent accounts for 0.1-0.5 wt%; and the thermosensitive intelligent control composite particles are prepared by doping metal compounds and performing composite nanocrystallization. The functional master batch can realize high infrared light transmission at low temperature and high infrared reflection at high temperature, is applied to the aspects of films, plates, fiber fabrics and the like, and can realize the functional effect of intelligent temperature control.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of thermosensitive intelligent control type functional masterbatch, and specifically to a thermosensitive intelligent control type functional masterbatch and a preparation method thereof. Background Art

[0002] The current thermal insulation masterbatch is used to produce thermal insulation films, plates, fibers and other products, mainly by absorbing and blocking sunlight in the infrared band to achieve thermal insulation effects. In practical applications, some demands are still difficult to meet. For example, in the cold winter, people hope that infrared light can penetrate into the interior space to obtain more heat; in the hot summer, people prefer to enhance the reflection ability of infrared light to trap more heat in the external space. This places higher demands on the functionality of the material, and it is difficult for general thermal insulation materials to achieve such stable and accurate conversion and regulation. Phase change materials have become the main material in this direction. Chinese patent CN117385489A discloses a composite structure phase change thermal storage fiber, which achieves thermal storage and warmth preservation functions by uniformly embedding high entropy vanadium-based shell phase change nano-microcapsules into the fiber matrix with a higher phase change enthalpy value (>15J / g). Chinese patent CN110741856A discloses a method for preparing an insect-proof and anti-aging sunshade net, which is prepared by doping vanadium pentoxide with lead molybdate and using a thermal reduction method to obtain a vanadium dioxide sunshade, and using carbon nanotubes to improve a certain degree of heat dissipation to achieve a sunshade function. On the basis of phase change materials, a safer and more environmentally friendly preparation method is used to prepare a functional material with more sensitive and comprehensive regulation and transformation, which can achieve further breakthroughs in functionality and practicality, open up broad application prospects, and also play a significant role in promoting energy conservation, emission reduction and social development. In summary, a new technical solution needs to be provided to solve the problem. Summary of the invention

[0003] In view of the shortcomings of the existing technology, a high-performance functional masterbatch is provided which can quickly and accurately regulate the changes in ambient temperature, so as to achieve its functional improvement and application expansion.

[0004] According to an embodiment, the present invention provides a thermosensitive intelligent control functional masterbatch, which is composed of a plastic matrix, thermosensitive intelligent control composite particles, and a coupling agent, wherein the plastic matrix accounts for 79.5-94.9wt%, the thermosensitive intelligent control composite particles account for 5-20wt%, and the coupling agent accounts for 0.1-0.5wt%; wherein the plastic matrix is ​​selected from polycaprolactam, polyethylene, polypropylene, polyvinyl chloride, polystyrene, polyethylene terephthalate, polymethyl methacrylate, polycarbonate, and the coupling agent is a titanate coupling agent.

[0005] Preferably, the method for preparing the thermosensitive intelligent control composite particles comprises the following steps:

[0006] (1) According to the mass ratio, 1-3 parts of butyl titanate are added to 30-80 parts of ethanol and stirred to form solution A; 0.02-0.0.05 parts of ammonium molybdate are added to 10-20 parts of ethanol and stirred to form solution B. The two solutions are mixed evenly, and a hydrochloric acid / acetic acid solution with a concentration of 0.1-0.3 mol / L is added, and the mixture is heated to 40-50° C. and stirred for 1-3 hours to form reactant C;

[0007] (2) 10-20 parts of ammonium vanadate, 0.1-0.5 parts of ammonium tungstate, and 0.01-0.05 parts of ammonium molybdate are added to 200-500 parts of ethanol in sequence and stirred evenly, 0.1-0.5 parts of polyethylene glycol are added, reactant C is added, a pH adjuster is added, and the mixture is heated to 45-55° C. and stirred for 24-36 hours;

[0008] (3) washing by centrifugation and drying, and calcining at 400-450° C. in an oxygen-free environment for 3-5 h to obtain reactant D;

[0009] (4) The reactant D is immersed in 1-2 mol / L hydrochloric acid for 1-2 h and then washed by centrifugation. It is then added to an equal volume mixed medium of 20-30 parts of ethanol and water containing 0.2-0.5 parts of graphene oxide, 0.05-0.1 parts of polyethylene glycol, and 0.1-0.3 parts of bis(dioctyl pyrophosphate)ethylene titanate. 0.01-0.1 parts of a colorant are added and wet grinding is performed until the medium evaporates. After vacuum drying, the thermosensitive intelligent control composite particles are obtained.

[0010] Preferably, in step (1) of the method for preparing thermosensitive intelligent control composite particles, the mass ratio of hydrochloric acid to acetic acid in the hydrochloric acid / acetic acid solution is (2-4):1, and the hydrochloric acid / acetic acid solution is added at a rate of 1-3 ml / min through a microinjection pump.

[0011] Preferably, in step (2) of the method for preparing thermosensitive intelligent control composite particles, the pH regulator is triethylamine, and the pH is adjusted to 8.5-10.

[0012] Preferably, in step (2) and step (4) of the method for preparing thermosensitive intelligent control composite particles, the molecular weight of polyethylene glycol is 1000-3000 g / mol.

[0013] Preferably, in step (4) of the method for preparing thermosensitive intelligent control composite particles, the particle size of graphene oxide is 10-30 nm; and the colorant is selected from pyrrolopyrrole dione derivatives, benzimidazolone derivatives, and phthalocyanine derivatives.

[0014] Compared with the prior art, the technical effects of the present invention are:

[0015] The present invention uses thermosensitive intelligent control composite particles as the main functional component, and adds them to the plastic matrix to obtain a thermosensitive intelligent control functional masterbatch, which can realize the control of the phase change temperature. When it is lower than the phase change temperature, infrared is transmitted, and when it is higher than the phase change temperature, infrared is reflected. This is mainly due to the preparation and application of molybdenum-tungsten doped tungsten oxide thermal phase change materials. On the other hand, molybdenum-doped titanium oxide materials can have high ultraviolet barrier properties, improve aging resistance, enhance infrared reflectivity, and further improve the spectral control effect of the functional masterbatch. At the same time, graphene oxide serves as both a dispersing material and a heat dissipation material, which greatly improves the high-definition heat insulation function of the functional masterbatch. The nano-functional material is further compounded with the resin matrix through a titanate coupling agent, realizing its stable existence in the resin matrix, and ensuring the realization and improvement of the functionality of the thermosensitive intelligent control functional masterbatch.

[0016] The thermal-sensitive intelligent control functional masterbatch prepared by the present invention has the following advantages: high infrared transmittance below the phase change temperature, high infrared reflection above the phase change temperature, good stability, and the film prepared therefrom has high transparency and high definition, and has extremely high application value in many fields such as automobiles, construction, agriculture, and textiles. DETAILED DESCRIPTION

[0017] The present invention will be further described below in conjunction with specific embodiments. These embodiments should be understood to be only used to illustrate the present invention and not to limit the scope of protection of the present invention. After reading the content of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent changes and modifications also fall within the scope defined by the claims of the present invention.

[0018] The other raw materials used in the following examples are all commercially available products unless otherwise specified.

[0019] Example 1

[0020] The preparation method of the thermosensitive intelligent control composite particles is as follows:

[0021] (1) 12 g of butyl titanate was added to 500 ml of ethanol and stirred to form solution A; 0.2 g of ammonium molybdate was added to 150 ml of ethanol and stirred to form solution B. The two solutions were mixed evenly, and a 0.3 mol / L hydrochloric acid / acetic acid solution (the mass ratio of hydrochloric acid to acetic acid was 3:1) was added through a microinjection pump at a rate of 1 ml / min, and the mixture was heated to 50° C. and stirred for 2 h to form a reactant C;

[0022] (2) 100 g of ammonium vanadate, 1 g of ammonium tungstate, and 0.5 g of ammonium molybdate were added to ethanol in sequence and stirred evenly, 5 g of polyethylene glycol with a molecular weight of 1000 g / mol was added, reactant C was added, triethylamine was added to adjust the pH to 9, and the mixture was heated to 55° C. and stirred for 24 h;

[0023] (3) Repeatedly centrifugally clean and dry, and calcined at 450°C in an oxygen-free environment for 4 h to obtain reactant D;

[0024] (4) The reactant D was immersed in 1 mol / L hydrochloric acid for 1 h and then washed by centrifugation. It was then added to an equal volume mixed medium of 240 ml ethanol and water containing 3 g of graphene oxide with a particle size of 20 nm, 1 g of polyethylene glycol with a molecular weight of 2000 g / mol, and 1 g of bis(dioctylpyrophosphate)ethylene titanate. 0.2 g of dipyrrolopyrrole was added and wet grinding was performed until the medium evaporated. After vacuum drying, the thermosensitive intelligent control composite particles were obtained.

[0025] 100g of thermal-sensitive intelligent control composite particles, 700g of polyethylene terephthalate plastic slices, and 0.5g of titanate coupling agent were fully stirred and added into a plastic granulator to obtain a thermal-sensitive intelligent control functional masterbatch.

[0026] Example 2

[0027] The preparation method of the thermosensitive intelligent control composite particles is as follows:

[0028] (1) 14 g of butyl titanate was added to 700 ml of ethanol and stirred to form solution A; 0.3 g of ammonium molybdate was added to 150 ml of ethanol and stirred to form solution B. The two solutions were mixed evenly, and a 0.3 mol / L hydrochloric acid / acetic acid solution (the mass ratio of hydrochloric acid to acetic acid was 4:1) was added through a microinjection pump at a rate of 1.5 ml / min, and the mixture was heated to 50° C. and stirred for 2 h to form a reactant C;

[0029] (2) 120 g of ammonium vanadate, 1.3 g of ammonium tungstate, and 0.3 g of ammonium molybdate were added to ethanol in sequence and stirred evenly, 5 g of polyethylene glycol with a molecular weight of 2000 g / mol was added, reactant C was added, triethylamine was added to adjust the pH to 9, and the mixture was heated to 55° C. and stirred for 36 h;

[0030] (3) Repeatedly centrifugally clean and dry, and calcined at 450°C in an oxygen-free environment for 4 h to obtain reactant D;

[0031] (4) The reactant D was immersed in 1 mol / L hydrochloric acid for 1 h and then washed by centrifugation. It was then added to an equal volume mixed medium of 270 ml ethanol and water containing 4 g of graphene oxide with a particle size of 10 nm, 1 g of polyethylene glycol with a molecular weight of 1000 g / mol, and 1.2 g of bis(dioctylpyrophosphate)ethylene titanate. 0.25 g of benzimidazolone H3R was added and wet grinding was performed until the medium evaporated. After vacuum drying, the thermosensitive intelligent control composite particles were obtained.

[0032] 100g of thermal-sensitive intelligent control composite particles, 700g of polyethylene terephthalate plastic slices, and 0.5g of titanate coupling agent were fully stirred and added into a plastic granulator to obtain a thermal-sensitive intelligent control functional masterbatch.

[0033] Example 3

[0034] The preparation method of the thermosensitive intelligent control composite particles is as follows:

[0035] (1) 20 g of butyl titanate was added to 800 ml of ethanol and stirred to form solution A; 0.5 g of ammonium molybdate was added to 200 ml of ethanol and stirred to form solution B. The two solutions were mixed evenly, and a 0.3 mol / L hydrochloric acid / acetic acid solution (the mass ratio of hydrochloric acid to acetic acid was 4:1) was added through a microinjection pump at a rate of 2 ml / min, and the mixture was heated to 50° C. and stirred for 3 h to form a reactant C;

[0036] (2) 150 g of ammonium vanadate, 1.5 g of ammonium tungstate, and 0.5 g of ammonium molybdate were added to ethanol in sequence and stirred evenly, 5 g of polyethylene glycol with a molecular weight of 2000 g / mol was added, reactant C was added, triethylamine was added to adjust the pH to 9, and the mixture was heated to 55° C. and stirred for 36 h;

[0037] (3) Repeatedly centrifugally clean and dry, and calcined at 450°C in an oxygen-free environment for 5 h to obtain reactant D;

[0038] (4) The reactant D was immersed in 1 mol / L hydrochloric acid for 2 h and then washed by centrifugation. It was then added to an equal volume mixed medium of 300 ml ethanol and water containing 5 g of graphene oxide with a particle size of 10 nm, 1 g of polyethylene glycol with a molecular weight of 1000 g / mol, and 1.8 g of bis(dioctylpyrophosphate)ethylene titanate. 0.2 g of phthalocyanine blue BGS was added and wet grinding was performed until the medium evaporated. After vacuum drying, the thermosensitive intelligent control composite particles were obtained.

[0039] 100g of thermal-sensitive intelligent control composite particles, 700g of polymethyl methacrylate plastic slices, and 0.5g of titanate coupling agent were fully stirred and added into a plastic granulator to obtain a thermal-sensitive intelligent control functional masterbatch.

[0040] Comparative Example

[0041] The preparation method of the thermosensitive intelligent control composite particles is as follows:

[0042] (1) 14 g of butyl titanate was added to 700 ml of ethanol and stirred to form solution A; 0.3 g of ammonium molybdate was added to 150 ml of ethanol and stirred to form solution B. The two solutions were mixed evenly, and a 0.3 mol / L hydrochloric acid / acetic acid solution (the mass ratio of hydrochloric acid to acetic acid was 4:1) was added through a microinjection pump at a rate of 1.5 ml / min, and the mixture was heated to 50° C. and stirred for 2 h to form a reactant C;

[0043] (2) 120 g of ammonium vanadate, 1.3 g of ammonium tungstate, and 0.3 g of ammonium molybdate were added to ethanol in sequence and stirred evenly, 5 g of polyethylene glycol with a molecular weight of 2000 g / mol was added, reactant C was added, triethylamine was added to adjust the pH to 9, and the mixture was heated to 55° C. and stirred for 36 h;

[0044] (3) Repeatedly centrifugally clean and dry, and calcined at 450°C in an oxygen-free environment for 4 h to obtain reactant D;

[0045] (4) The reactant D was immersed in 1 mol / L hydrochloric acid for 1 h and then washed by centrifugation. It was added to an equal volume mixed medium of 270 ml ethanol and water containing 4 g of graphene oxide with a particle size of 10 nm and 1 g of polyethylene glycol with a molecular weight of 1000 g / mol. 0.2 g of dione pyrrolopyrrole was added and wet grinding was performed. The medium was volatilized and vacuum dried to obtain thermosensitive intelligent control composite particles.

[0046] 100g of thermal-sensitive intelligent control composite particles, 700g of polyethylene terephthalate plastic chips, and 0.5g of titanate coupling agent were fully stirred and added into a plastic granulator to obtain a thermal-sensitive intelligent control functional masterbatch.

[0047] Test example

[0048] The thermosensitive intelligent control functional masterbatch prepared in each embodiment and comparative example was blended and extruded with the corresponding base material masterbatch at a mass ratio of 10%, and a film with a thickness of 50 μm was prepared to test its performance.

[0049] The infrared blocking rate of the film samples was tested at 25°C and 45°C (the measurement point was selected at 1400nm), and the haze and aging resistance of the samples were tested. The change in infrared blocking rate was tested at different temperatures using the Linshang LS182 optical transmittance meter; to control different temperatures, the test was carried out in a constant temperature and humidity chamber, and the temperatures were adjusted to 25°C and 45°C and stabilized for 1h in advance. The test wavelength was 1400nm. The haze was tested using a Languang WGT-S haze meter, and the test was carried out at room temperature. The aging resistance was tested using a Kejian KJ-9029 UV accelerated test chamber with an ultraviolet wavelength of 340nm. The samples were irradiated with 4 40W UV lamps for testing. The samples were placed 50mm away from the lamps, and the irradiance was approximately 50W / m 2, 4h ultraviolet illumination and 4h condensation were carried out alternately, and the temperature was maintained at 50℃. The results show that the infrared blocking rate of the film sample changes significantly with the increase of temperature, from 80-83% at 25℃ to 90-92% at 45℃, which shows that its thermal phase change improves the infrared blocking performance of the sample. At the same time, the haze of each embodiment sample is <1%, while the haze of the comparative sample is higher than that of the embodiment sample. This is mainly because the comparative sample is not pretreated with bis(dioctyl pyrophosphate acyloxy)ethylene titanate, which is prone to problems of microscopic phase separation and migration of particles, resulting in its dispersibility being inferior to other samples. For similar reasons, after 500h ultraviolet rapid aging test, the clarity of each embodiment sample did not change significantly, while the haze of the comparative sample increased. The above tests show that the thermal-sensitive intelligent control functional masterbatch prepared by each embodiment has temperature responsiveness and can improve thermal insulation performance as the temperature increases; at the same time, it also maintains good clarity and stability, and has important application value in intelligent temperature control, energy saving and emission reduction.

[0050] Table 1 Performance test of films prepared in Examples and Comparative Examples

[0051]

[0052] The above content is a detailed description of the present invention in combination with specific embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For those skilled in the art of the present invention, without departing from the concept of the present invention, several simple deductions or substitutions can be made, which should be regarded as falling within the scope of protection of the present invention.

Claims

1. A thermal-sensitive intelligent control functional masterbatch and a preparation method thereof, characterized in that: The masterbatch is composed of a plastic matrix, thermosensitive intelligent control composite particles, and a coupling agent, wherein the plastic matrix accounts for 79.5-94.9wt%, the thermosensitive intelligent control composite particles account for 5-20wt%, and the coupling agent accounts for 0.1-0.5wt%; wherein the plastic matrix is ​​selected from polycaprolactam, polyethylene, polypropylene, polyvinyl chloride, polystyrene, polyethylene terephthalate, polymethyl methacrylate, polycarbonate, and the coupling agent is a titanate coupling agent; The preparation method of the thermosensitive intelligent control functional masterbatch is as follows: (1) According to the mass ratio, 1-3 parts of butyl titanate are added to 30-80 parts of ethanol and stirred to form solution A; 0.02-0.0.05 parts of ammonium molybdate are added to 10-20 parts of ethanol and stirred to form solution B. The two solutions are mixed evenly, and a hydrochloric acid / acetic acid solution with a concentration of 0.1-0.3 mol / L is added, and the mixture is heated to 40-50°C and stirred for 1-3 hours to form reactant C; (2) 10-20 parts of ammonium vanadate, 0.1-0.5 parts of ammonium tungstate, and 0.01-0.05 parts of ammonium molybdate are added to 200-500 parts of ethanol in sequence and stirred evenly, 0.1-0.5 parts of polyethylene glycol are added, reactant C is added, a pH adjuster is added, and the mixture is heated to 45-55° C. and stirred for 24-36 hours; (3) washing by centrifugation and drying, and calcining at 400-450° C. in an oxygen-free environment for 3-5 h to obtain reactant D; (4) The reactant D is immersed in 1-2 mol / L hydrochloric acid for 1-2 h and then washed by centrifugation. It is then added to an equal volume mixed medium of 20-30 parts of ethanol and water containing 0.2-0.5 parts of graphene oxide, 0.05-0.1 parts of polyethylene glycol, and 0.1-0.3 parts of bis(dioctyl pyrophosphate)ethylene titanate. 0.01-0.1 parts of a colorant are added and wet grinding is performed until the medium evaporates. After vacuum drying, the thermosensitive intelligent control composite particles are obtained.

2. The method for preparing the thermosensitive intelligent control functional masterbatch according to claim 1, characterized in that: In step (1), the mass ratio of hydrochloric acid to acetic acid in the hydrochloric acid / acetic acid solution is (2-4):1, and the hydrochloric acid / acetic acid solution is added at a speed of 1-3 ml / min through a microinjection pump.

3. The method for preparing the thermosensitive intelligent control functional masterbatch according to claim 1, characterized in that: The pH regulator in step (2) is triethylamine, and the pH is adjusted to 8.5-10; the molecular weight of the polyethylene glycol in step (2) and step (4) is 1000-3000 g / mol.

4. The method for preparing the thermosensitive intelligent control functional masterbatch according to claim 1, characterized in that: In step (4), the particle size of graphene oxide is 10-30 nm; in step (4), the toner is selected from pyrrolopyrrole dione derivatives, benzimidazolone derivatives, and phthalocyanine derivatives.

Citation Information

Patent Citations

  • Pest-proof anti-aging sunshade net preparation method

    CN110741856A

  • Phase change heat storage fiber with composite structure and preparation method of phase change heat storage fiber

    CN117385489A

Cited By

  • Vanadium dioxide-phthalocyanine-graphene composite material and preparation method thereof

    CN117742057A

  • Vanadium dioxide-phthalocyanine-graphene composite material and preparation method thereof

    CN117742057B